2024
DOI: 10.3847/1538-3881/ad29f9
|View full text |Cite
|
Sign up to set email alerts
|

CLusters in the Uv as EngineS (CLUES). II. Subkiloparsec-scale Outflows Driven by Stellar Feedback

Mattia Sirressi,
Angela Adamo,
Matthew Hayes
et al.

Abstract: We analyze the far-ultraviolet (1130−1770 Å rest frame) spectroscopy of 20 young (<50 Myr) and massive (>104 M ⊙) star clusters (YSCs) in 11 nearby star-forming galaxies. We probe the interstellar gas intervening along the line of sight, detecting several metal absorption lines of a wide range of ionization potentials, from 6.0 to 77.5 eV. Multiple-component Voigt fits to the absorption lines are used to study the kinematics of the gas. We find that nearly all targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Our Starburst99 simulation suggests that the YMCs can together produce a mechanical luminosity of ∼2 × 10 40 erg s −1 , or a total deposited mechanical energy of ∼3 × 10 54 erg over 4 Myr. A mere 2% energy retention factor (easily reachable for stellar wind and supernova-driven outflows; see Kim et al 2020;Sirressi et al 2024) would be enough to power the ionized gas outflow reported by Leaman et al (2019) and to heat the X-ray emitting gas studied by Swartz et al (2006). These order-of-magnitude calculations suggest that the current population of YMCs will be more than capable of driving gas outflow at a similar level in the future.…”
Section: Ymcs In Large-scale Contextmentioning
confidence: 99%
“…Our Starburst99 simulation suggests that the YMCs can together produce a mechanical luminosity of ∼2 × 10 40 erg s −1 , or a total deposited mechanical energy of ∼3 × 10 54 erg over 4 Myr. A mere 2% energy retention factor (easily reachable for stellar wind and supernova-driven outflows; see Kim et al 2020;Sirressi et al 2024) would be enough to power the ionized gas outflow reported by Leaman et al (2019) and to heat the X-ray emitting gas studied by Swartz et al (2006). These order-of-magnitude calculations suggest that the current population of YMCs will be more than capable of driving gas outflow at a similar level in the future.…”
Section: Ymcs In Large-scale Contextmentioning
confidence: 99%